The Role of Bhabinkamtibmas in Efforts to Press the Spread of the Virus Covid-19 - Pohan, Ibrahim; Sriono, Sriono; Kumalasari M, Indra (Budapest International Research and Critics University, 2021)
The increasing number of Covid-19 sufferers in various parts of the world to districts, and creating new clusters due to community non-compliance with health protocols. The increase in Covid-10 cases has an impact on the occurrence of criminal cases that need serious handling from the authorities. The police use a preventive approach to support the implementation of health protocols during the Covid-19 pandemic in order to reduce the spread of the Coid-19 virus through the activities of Bhabinkamtibmas personnel. Efforts to prevent the Spread of the Corona Virus (Covid-19) continue to be carried out by Personal Bhabinkamtibmas in the Labuhanbatu Police area, namely actively socializing the dangers of Covid-19 through activities of swan visits, socialization, education, mask raids, and installation of banners to campaign health protocols to the public such as wearing masks, wash your hands and keep your distance. Bhabinkamtibmas also synergizes with Babinsa (TNI) in suppressing the spread of Covid-19. These activities are in the context of realizing a reduction in the transmission of the Covid-19 case, increasing people's purchasing power, decreasing crime rates, and in the end security and public order (kamtibmas) can be conducive.